2014 IEEE Eighth International Conference on Self-Adaptive and Self-Organizing Systems Workshops 2014
DOI: 10.1109/sasow.2014.28
|View full text |Cite
|
Sign up to set email alerts
|

Robust Self-Monitoring in Trusted Desktop Grids for Self-Configuration at Runtime

Abstract: A Trusted Desktop Grid System (TDG) is a platform for autonomous agents to share their computing resources based on trust relationships. Thereby, agents that only use the system without a fair participation are considered as malicious. Typically, the effects of active malicious agents and high-load situations of the TDG are similar -calling for appropriate approaches to distinguish them and, thus, allowing for counter measures to attacks. In this paper, we investigate the effect of high load to our measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the context of computational trust, a concept for establishing explicit communities of mutually trusted subsystems and isolating malicious or faulty subsystems has been presented [95]. Based on this initial concept, several extensions have been investigated: Mechanisms for measuring trust and reputation [96], advanced attacks on such trust communities and corresponding countermeasures [97], accusation-based strategies to identify misbehaving subsystems and to establish forgiveness solutions [98], and robust self-monitoring mechanisms at run-time [99]. Furthermore, [100] demonstrated that computational trust and forgiveness techniques can result in improved reliability and reduced overhead.…”
Section: Integration Aspectsmentioning
confidence: 99%
“…In the context of computational trust, a concept for establishing explicit communities of mutually trusted subsystems and isolating malicious or faulty subsystems has been presented [95]. Based on this initial concept, several extensions have been investigated: Mechanisms for measuring trust and reputation [96], advanced attacks on such trust communities and corresponding countermeasures [97], accusation-based strategies to identify misbehaving subsystems and to establish forgiveness solutions [98], and robust self-monitoring mechanisms at run-time [99]. Furthermore, [100] demonstrated that computational trust and forgiveness techniques can result in improved reliability and reduced overhead.…”
Section: Integration Aspectsmentioning
confidence: 99%
“…Most multi-agent system based adaptation relies on the distributed and autonomous nature of the constituent agents [11], but there is little literature on how to configure the agents themselves. Applications such as collision avoidance [6], grid management [16] use collaborative learning, and hierarchically deferring to a controller agent, to achieve the application's objectives. The most popular technique of self-configuration in multi-agent systems is reinforcement-learning [4].…”
Section: Introductionmentioning
confidence: 99%